North American Contact Dermatitis Group Patch Test Results 2013–2014. Issue 1 (January 2017) - DeKoven, Joel G.; Warshaw, Erin M.; Belsito, Donald V.; Sasseville, Denis; Maibach, Howard I.; Taylor, James S.; Marks, James G.; Fowler, Joseph F.; Mathias, C.G. Toby; DeLeo, Vince A.; Pratt, Melanie D.; Zirwas, Matthew J.; et al.
Abstract : Background: Patch testing is the most important diagnostic tool for the assessment of allergic contact dermatitis. Objective: This study documents the North American Contact Dermatitis Group (NACDG) patch testing results from January 1, 2013, to December 31, 2014. Methods: At 13 centers in North America, patients were tested in a standardized manner with a screening series of 70 allergens. Data were manually verified and entered into a central database. Descriptive frequencies were calculated, and trends were analyzed using χ 2 test. Results: A total of 4871 patients were tested. There were 3255 patients (66.8%) who had at least 1 positive reaction and 2412 patients (49.5%) who were ultimately determined to have a primary diagnosis of allergic contact dermatitis. A total of 434 patients (8.9%) had occupationally related skin disease. There were 9726 positive allergic reactions. Compared with the previous reporting periods (2011–2012 and 2001–2012, including at least three 2-year cycles), positive reaction rates for the top 25 screening allergens statistically increased for 2 allergens: methylchloroisothiazolinone/methylisothiazolinone (6.4%; risk ratios, 1.26 [1.07–1.50] and 2.08 [1.84–2.37]) and hydroxyethyl methacrylate (2.6%; risk ratios, 1.34 [1.02–1.76] and 1.23 [1.00–1.51]). Methylisothiazolinone, which was added to the screening series for this 2013–2014 cycle, had the third highest positive reaction rate of allergens tested (10.9%). Four other newly added allergen preparations—formaldehyde 2% (7%), diphenylguanidine (3.8%), propylene glycol 100% (2.8%), and benzophenone-4 (2.1%)—all had reaction rates greater than 2%. Twenty-one percent of tested patients had at least 1 relevant allergic reaction to an allergen not on the NACDG series; 14.6% of these were occupationally related. The T.R.U.E. TEST (SmartPractice Denmark, Hillerød, Denmark) would have hypothetically missed one quarter to one third of reactions detected by the NACDG screening series. Conclusions: These results confirm that the epidemic of sensitivity to methylisothiazolinone previously documented in Europe is also occurring in North America. Patch testing with allergens beyond a standard screening tray is necessary for the complete evaluation of occupational and nonoccupational allergic contact dermatitis.